CORPORATE GOVERNANCE, KARAKTERISTIK PERUSAHAAN DAN KINERJA KEUANGAN PERUSAHAAN - Malau, Joel Pardin; Widiatmoko, Jacobus; Indarti, MG. Kentris (Proceeding SENDI_U, 2019)
This study aims to examine the effect of corporate governance, liquidity, and company growth on financial performance in companies that are included in corporate governance perception indexs and are listed on the Indonesia Stock Exchange during 2014-2017. By using purposive sampling method obtained data as much as 56. The results of hypothesis testing indicate that corporate governance and liquidity have a positive effect on the company's financial performance. As good as the governance and the more liquid a company is, the better the financial performance. Conversely, the company's growth is not proven to affect the company's financial performance. Keywords: Good Corporate Governance, Liquidity, Company Growth, and financial performance